Quality of alveolar bone - Structure dependant material properties and design of a novel measurement technique - Winter, Werner; Steinmann, Paul; Wichmann, Manfred; et al. (IFMBE Proceedings 31, 2010)
In a first part, the aim of this paper is to describe the biomechanical background which can be used as a basis for determining bone quality by measuring elastic properties of bone. Applying material mechanical equations for porous and cellular structured models, the elastic material properties (modulus of elasticity) of cellular and cortical bone as porous structures were approximated over the whole range of relative bone mineral density 0
UnivIS-Import:2017-07-10:Pub.2010.tech.FT.FT-TM.qualit
Keywords: Bone density; bone quality; compressive testing; dental implant; elastic modulus